sulfonated polystyrene pore-filled electrolytes membranes by electrons induced grafting of styrene into PVDF films: thermal stability and structural investigation - Zubir, Nor Aida; Ismail, Ahmad Fauzi; Dahlan, Khairulzaman Haji Mohd; Nasef, Mohamed Mahmoud El-Sayed; Saidi, Hamdani (Penerbit Universiti Sains Malaysia, 2004)
There is considerable interest currently in pore-filled electrolyte membranes (Mika et al., 1995, Yamaguchi et al., 2003). These membranes have a variety of potential applications such as temperature and pH (ionic strength) sensors (Childs et al., 2002), dialysis (Stachera et al., 1998), proton exchange membrane (Bae and Kim., 2003, Yamaguchi et al., 2003;) and so on. Efforts have been made in order to study and correlate the performance of such membranes with the grafting yield in these systems.